Quality Improvement of Subgrade Through Intelligent Compaction. Issue 1 (2016) - Barman, Manik; Nazari, Moeen; Imran, Syed Asif; Commuri, Sesh; Zaman, Musharraf
Proper quality control and quality improvement strategies during compaction can improve the quality of the subgrade and minimize premature failures of asphalt pavements. This paper discusses the use of the Intelligent Compaction Analyzer (ICA), which was developed at the University of Oklahoma, in quality control and quality improvement during compaction of stabilized subgrade. Six case studies were conducted to demonstrate the ability of the ICA in monitoring subgrade density and subgrade modulus (known as ICA modulus) in real time. The ICA modulus correlated reasonably with the subgrade modulus backcalculated from the falling weight deflectometer data ( R 2 = .63), fairly with the dynamic cone penetrometer test results ( R 2 = .50), and excellently with the in situ subgrade resilient modulus ( R 2 = .72 to .97). The subgrade modulus in undercompacted areas could be increased by more than 50% by applying additional roller passes.